Environmental and health risks associated with reuse of wastewater for irrigation - Eman Shakir; Zahraa Zahraw; Abdul Hameed M.J. Al-Obaidy (Egyptian Journal of Petroleum)
The present study focuses on the environmental and health risks associated with the use of treated wastewater produced from Al-Rustamia third extension plant for irrigation. The measured data are used to evaluate comprehensive pollution index (CPI) and organic pollution index (OPI). The average CPI was found as 0.69 which indicated to be slightly polluted for all seasons and a similar result was also obtained with OPI, which is found to slightly vary in the range 1.29–1.60 which indicates as being to be contaminated. Also to evaluate its suitability for irrigation purposes, Sodium Adsorption Ratio (SAR), Soluble Sodium Percentage (SSP) and Residual Sodium Carbonate (RSC) were calculated following standard equations and found experimentally as (8.70), (74.76) and (2.68) respectively. Irrigation water classes are used for Salinity hazard (EC) and Sodium hazard (SAR) to assess water suitability for irrigation, and it is found that samples in summer and autumn in the class of C3-S1, indicate high salinity and low sodium water, while in spring and winter in the class of C4-S1, they indicate very high-salinity. Furthermore, the data indicate a slight to moderate degree of restriction on the use of this treated wastewater in irrigation due to chloride hazard. RSC value is more than 1.25 at all seasons, indicating that samples in summer and autumn are doubtful for irrigation purposes, while the samples in spring and winter are unsuitable for irrigation.